Assessment of Pyroptosis-Related Indicators as Potential Biomarkers and Their Association with Severity in Patients with Liver Cirrhosis - Wang D (Dove Medical Press, 2021)
Ding Wang,1,* Xi Zhan,1,* Rui Wu,2 Yan You,3 Weixian Chen,1 Liang Duan1 1Department of Laboratory Medicine, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Laboratory Medicine, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 3Department of Pathology, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liang Duan; Weixian ChenDepartment of Laboratory Medicine, The Second Affiliated Hospital of Chongqing Medical University, No. 74 Linjiang Road, Yu Zhong District, Chongqing, People’s Republic of ChinaTel/Fax +86-023-63693193; +86-023-63693701Email duanliang@cqmu.edu.cn; chenweixian75@163.comPurpose: The diagnosis and management of liver cirrhosis remain challenging due to its diverse clinical manifestations and elusive severity evaluation. Pyroptosis, an identified inflammatory form of cell death, has recently been reported to participate in cirrhosis development. Nonetheless, the clinical significance of pyroptosis in liver cirrhosis remains largely unexplored.Patients and Methods: One hundred and fifty-one liver cirrhosis patients either alone or in combination with various complications and twenty-nine gender- and age-matched healthy controls (HCs) were enrolled in this study. Pyroptosis-related indicators gasdermin D (GSDMD), IL-1ß and IL-18 were measured by IHC in tissue section and by ELISA in serum, respectively, and correlations of their circulating levels with disease severity as well as their potential as biomarkers for monitoring cirrhosis progression were evaluated.Results: Increased levels of the circulating pyroptosis-related indicators GSDMD, IL-1ß and IL-18 were observed in liver cirrhosis patients, especially those with an etiology of viral infection. In addition, all three indicators were positively correlated with disease severity parameters, including Child-Pugh classification, APRI scores and compensated status. Furthermore, receiver operating characteristic (ROC) analysis showed that circulating IL-1ß exerted potential discriminating power for SBP occurrence in liver cirrhosis, but GSDMD possessed differentiating power for SBP in liver cirrhosis with ascites, which yielded area under the ROC curve (AUC) of 0.81 and 0.80, respectively.Conclusion: Liver cirrhosis patients exhibited increased levels of circulating GSDMD, IL-1ß and IL-18, all of which were positively correlated with disease severity. More importantly, the identified circulating IL-1ß and GSDMD exhibited potentials as novel biomarkers for liver cirrhosis patients presenting with SBP.Keywords: GSDMD, IL-1ß, IL-18, liver cirrhosis, severity, complication